The EU Trustworthy Artificial Intelligence: How the EU Wants to Regulate the Artificial Intelligence Practices - Rodríguez Cuadros, Miguel Adolfo (2021)
The European Union (EU) recently proposed in April 2021 an Artificial Intelligence legal framework. The EU highlights the advantages of using Artificial Intelligence (AI) especia-lly in prediction, optimizing operations, resource allocation and personalizing service delivery. Nevertheless, the EU considers that AI might bring new risks and negative consequences for individuals and society when an AI system violates the EU values and fundamental rights. This paper explains how the EU is proposing a legal framework for trustworthy AI. Tech or nontech companies and professionals should know what kind of AI applications and practices might be prohibited or restricted within the EU. More specifically, this paper focuses on what type of AI system can be considered unacceptable risk, high or low risk AI.